Effectiveness of Concept Mapping’s Efficiency in Differential Equations - Fatemeh (Uni-pluriversidad, 2020)
One of the existing approaches in students’ performance evaluation is to use concept mapping. There are lots of studies indicate that concept mappings can be used to evaluate the knowledge of mathematical concepts in a useful way. The best and most comprehensive way of learning is organizing study. Organizing is an expanding meaning strategy. Concept mapping is a simple way to organize and relate information, if vaguely. Lines, words, signs, and symbols are used in concept mappings. In this study, the use of concept mappings in differential equations has been investigated. To do so, a case study of understanding differential equations unit has been conducted in 90 students from Azad University. To begin with, the students went under seven sessions of differential equations of grade one, and another group was taught differential equations in a traditional way. After that, the results obtained were evaluated using SPSS software and Mann-Whitney U test to reach the conclusion. The results indicate the effectiveness of concept mappings. The students show ability to recognize the structure of differential equations that cannot be seen in the results of a traditional teaching method. In addition, the misunderstandings in misconceptions of such structures can be revealed. Therefore, it can be recommended to use the concept maps about differential equations as a complementary assessment tool along with common written tests.